HUBUNGAN SIKAP, INFORMASI, DUKUNGAN KELUARGA TERHADAP PERILAKU DETEKSI DINI KANKER PAYUDARA PADA REMAJA KELAS X MADRASAH ALIAH KAIMANA PAPUA BARAT TAHUN 2021: The Relationship Of Attitudes, Information, Family Support Towards Early Detection Behavior Of Breast Cancer In Adolescents Of Class X Madrasah Aliah Kaimana West Papua 2021 - welkok, iqramirahma (Jurnal Ilmiah Kebidanan (Scientific Journal of Midwifery), 2023)
are in the same direction as the nipples and their tissue surrounds the ducts, blood vessels and lobules in the breast. Early detection of breast cancer is a person's attempt to be able to find out the disease by means of examination with several predetermined procedures so that it can be seen clearly whether a person has an abnormality. The general aim is to find out the relationship between family support, information, attitudes towards the behavior of early detection of breast cancer in class X young women at Madrasah Aliyah Kaimana West Papua in 2021. The research design used was cross-sectional. The population in this study was class X youth with a total of 85 respondents. The type of research used is quantitative and the data that can be used is primary data taken by filling out a questionnaire. Sampling using total sampling method. Using univariate and bivariate analysis with the chi square statistical test. The results of the univariate analysis found that there were more adolescents in Madrasah Aliyah who answered adequately. The behavior of early detection of breast cancer, the most attitudes answered negatively, the most answered information was incomplete and the most family support answered quite supportive. In the chi square test, the relationship between attitude and p-value = 0.002, the information relationship p-value = 0.000, the relationship between family support and the p-value = 0.000. The conclusion is that there is a relationship between attitudes, information, and family support for the behavior of early detection of breast cancer in students at the Madrasah Aliyah Kaimana West Papua in 2021. So it is suggested that it is necessary to increase the frequency of outreach about environmental attitudes, information, family support for the behavior of early detection of breast cancer